2020 IEEE 45th Conference on Local Computer Networks (LCN) 2020
DOI: 10.1109/lcn48667.2020.9314774
|View full text |Cite
|
Sign up to set email alerts
|

User Performance in a 5G Multi-connectivity Ultra-Dense Network City Scenario

Abstract: Multi-connectivity and network densification are two solutions intended to improve performance and reliability. These solutions can improve 5G NR's system performance especially when using high-frequency bands. This work focuses on the user equipment (UE) performance using multi-connectivity within an ultra-dense deployment in a city environment. By being connected to more than one access node simultaneously, the UE should benefit from increased reliability and performance. However, this improved performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In [5], the authors show how the loss of line-of-sight affects the network throughput. Similarly, it has been shown that in ultra-dense urban scenarios [4], [9], [10] and indoor scenarios [11], MC increases the per-user throughput. Our work differs from these papers in the sense that we consider not only loss of line-of-sight, but a more general class of link failures, based on for example distance or number of links to a certain BS.…”
Section: Related Workmentioning
confidence: 83%
“…In [5], the authors show how the loss of line-of-sight affects the network throughput. Similarly, it has been shown that in ultra-dense urban scenarios [4], [9], [10] and indoor scenarios [11], MC increases the per-user throughput. Our work differs from these papers in the sense that we consider not only loss of line-of-sight, but a more general class of link failures, based on for example distance or number of links to a certain BS.…”
Section: Related Workmentioning
confidence: 83%
“…In [4] and [9], the authors show how the loss of LoS affects the network throughput. Similarly, it has been shown that in ultra-dense urban scenarios [5], [10], [11], indoor scenarios [12] and under mobility [13], MC increases the per-user throughput. Our work differs from these papers in that we consider not only loss of LoS but a more general class of link failures, based on for example distance and channel impairments.…”
Section: Related Workmentioning
confidence: 85%
“…While the promise of MC over SC is demonstrated in the prior works such as [4], [5], a key question remains to find the optimal degree of MC, i.e., the number of connections per user, so that the throughput and network reliability is high. Since MC results in various complexities such as signalling overhead among multiple network nodes, traffic scheduling or combining at the receiver [2], it is desirable to find the degree of MC that achieves a significant improvement over a one-lower connectivity.…”
mentioning
confidence: 99%
“…Ultra-high data rates have been identified as a key aim goal for future production of wireless mobile networks. Successively to meet with increasing information transfer tariff, mobile device power consumption increases [5]. SWIPT is being offered as a constant source of power for cellular workstations, therefore boosting the standards of customer's comfort, as a result of the restricted battery lifespan of cellular gadgets.…”
Section: Energy Capture and Transfermentioning
confidence: 99%